Molecular Modelling Analysis of the Interaction Between Iron(III) and L-Cysteine in Solution in Water at Low pH - Huq, Fazlul; C.R. Peter, Marie (Asian Journal of Chemistry, 2010)
The interaction between iron(III) and L-cysteine, an amino acid, in solution in water at low pH has been investigated by UV-Visible spectrophotometry using the technique of continuous variation and molecular modelling. The absorbance value at λmax was plotted against concentrations of reactants. The maximum in the absorbance vs. concentration graph gave the ratio at which Fe3+ and L-cysteine combined. At low pH, iron(III) is found to form predominantly 1 : 1 complex with L-cysteine in which iron has a distorted tetrahedral coordination geometry. In the complex, cysteine acts as a tridentate ligand being bonded to Fe(III) through amino nitrogen, carboxyl oxygen and deprotonated sulfhydryl group. The fourth position in the coordination geometry is occupied by a water molecule. The proposed structure of the complex has been optimized and its electronic spectrum generated based on molecular mechanics and semi-empirical calculations. Comparison of the observed and predicted electronic spectra of the complex indicates that iron(III) in the complex is in the high spin state with a spin multiplicity of 6.